2021
DOI: 10.1002/slct.202102475
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Mg‐Based Hydrogen Storage Materials by Metal Catalysts: Review and Summary

Abstract: Magnesium hydride (MgH 2 ) has become a very promising hydrogen storage material because of its high hydrogen storage capacity, good reversibility and low cost. However, high thermodynamic stability and slow kinetic performance of MgH 2 limit its practical application. In the past few decades, many alternative methods have been designed to solve this problem. A large number of studies have demonstrated that the use of metal catalyst doping modification, MgH 2 nanocrystallization and other methods can greatly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 135 publications
0
5
0
Order By: Relevance
“…The high hydrogen storage capacity, good reversibility, and low cost of these alloys make them attractive candidates for on-board hydrogen storage systems. However, the high desorption temperature and slow kinetics of magnesium-based alloys remain significant challenges for their practical application in hydrogen-powered vehicles [ 148 ]. The development of advanced magnesium-based alloys with improved thermodynamic and kinetic properties, as well as the integration of these alloys into efficient and compact hydrogen storage systems, are crucial for their successful implementation in the automotive industry [ 149 ].…”
Section: Applications and Future Perspectivesmentioning
confidence: 99%
“…The high hydrogen storage capacity, good reversibility, and low cost of these alloys make them attractive candidates for on-board hydrogen storage systems. However, the high desorption temperature and slow kinetics of magnesium-based alloys remain significant challenges for their practical application in hydrogen-powered vehicles [ 148 ]. The development of advanced magnesium-based alloys with improved thermodynamic and kinetic properties, as well as the integration of these alloys into efficient and compact hydrogen storage systems, are crucial for their successful implementation in the automotive industry [ 149 ].…”
Section: Applications and Future Perspectivesmentioning
confidence: 99%
“…The reversible hydrogen storage capacity of Mg/MgH 2 can reach approximately 7.6 wt.%, which satisfies DOE’s regulations [ 1 , 5 , 6 , 34 ]. However, the hydrogen storage performance of Mg/MgH 2 has certain drawbacks, such as high thermodynamic stability (enthalpy ~76 kJ/mol and entropy ~130 kJ/mol [ 35 ]), slow hydrogen absorption/desorption kinetics and high temperature of hydrogen absorption/desorption, which are the main reasons why Mg/MgH 2 is difficult to be used on a large scale. Under atmospheric pressure, the dehydrogenation temperature of MgH 2 is over 300 °C; the temperature required for the reaction of magnesium with hydrogen to form MgH 2 exceeds 300 °C when the hydrogen pressure exceeds 3 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the chemical bond of MgH 2 (Mg-H) is too stable resulting in an activation energy (Ea) of about 160 kJ/mol for the dehydrogenation reaction of MgH 2 . Excitingly, due to the good exploitability of Mg/MgH 2 , scholars have been able to significantly improve its hydrogen storage performance through a series of measures, mainly including alloying treatment, nano-treatment and catalyst doping [ 34 , 35 , 36 , 37 ]. Alloying treatment and nanosizing treatment can effectively reduce the thermodynamic stability of Mg/MgH 2 , while both have very limited contribution to the kinetic performance of Mg/MgH 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the storage of hydrogen in hydride-forming metals is accompanied with drawbacks, the solution of which has received considerable attention from researchers. Thus, over the past decade, a large number of catalytic alloying additives have been identified that can improve the behavior of metal hydrides during hydrogen sorption and desorption reactions [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%